Restless skies at the turn of the first Millennium AD. Climate fluctuations, astronomic phenomena and socio-political turbulences in 10th and 11th century Byzantium and Japan in comparative perspective - Preiser-Kapeller, Johannes (De Medio Aevo, 2024)
Around the turn of the first Millennium AD, both in Christian polities such as the Byzantine Empire as well as in regions with Buddhist communities such as in Heian Japan, expectations of an end of times emerged. Although based on different religious and independent chronological interpretations, they gained attraction at the same time due to the parallel observation and interpretation of the same astronomical phenomena (such as sightings of Halley´s comet in 989 AD) or of simultaneous climate anomalies, which can partly be connected with the Oort Solar Minimum of the 11th century. This paper explores and compares the interplay between natural phenomena, religious and political unrest, apocalyptic interpretations and individual decision-making for Byzantium and Japan on the basis of historical and natural scientific evidence.